Growth of infants assisted in nursing appointments in childcare - Grazielle Cavalcante de Souza Carneiro; Lívia Maria Correia de Morais; Leidiane Francis de Araújo Costa; Talita Helena Monteiro de Moura; Marly Javorski; Luciana Pedrosa Leal
This study aimed to describe the growth during the introduction of complementary feeding to infants assisted in the nursing appointment in childcare. It is a descriptive, cross-sectional, quantitative study developed through research in 51 medical records of children aged 4-8 months, from September to October 2012 in a university hospital in the city of Recife, PE. Data were analyzed using Epi Info software, version 6.04 and described in simple and relative frequencies. It was found that for 33% of the children. complementary foods were introduced at six months. Of these, 88.2%, 69.2% and 57.1% showed ascending weight-for-age growth curves, and 88.2%, 66.7% and 71.4% ascending length-for-age growth curves at six, seven and eight months respectively. Children with appropriate and timely introduction of complementary feeding showed upward growth curves and adequate nutritional status.